2022
DOI: 10.1177/20552076221143236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mobile health interventions in increasing utilization of Maternal and Child Health care services in developing countries: A scoping review

Abstract: Background Mobile health (mHealth) technology is being used predominantly in low- and middle-income countries. Developing countries with low level of investment in health infrastructure can augment existing capacity by adopting low-cost affordable technology. The aim of the review was to summarize the available evidence on mHealth interventions that aimed at increasing the utilization of Maternal and Child Health (MCH) care services. Further, this review investigated the barriers which prevent the use of mHeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Multiple studies have indicated that mobile health (mHealth) interventions can improve access to MCH services. A meta-analysis in developing countries indicated that mobile phone reminders were beneficial [15,19] The odds of being vaccinated were 2.39 times greater among mothers who had attended at least one ANC visit than among mothers who had not attended ANC follow-up. This finding is in agreement with other studies conducted in Ethiopia [16,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have indicated that mobile health (mHealth) interventions can improve access to MCH services. A meta-analysis in developing countries indicated that mobile phone reminders were beneficial [15,19] The odds of being vaccinated were 2.39 times greater among mothers who had attended at least one ANC visit than among mothers who had not attended ANC follow-up. This finding is in agreement with other studies conducted in Ethiopia [16,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis in developing countries indicated that mobile phone reminders were beneficial [15,19] The odds of being vaccinated were 2.39 times greater among mothers who had attended at least one ANC visit than among mothers who had not attended ANC follow-up. This finding is in agreement with other studies conducted in Ethiopia [16,19,20]. This could be related to the counseling given at health facilities during ANC follow-up, which may bring about the desired behavioural change toward vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Kabongo et al (2021) described that m-health significantly associated with maternal and child healthcare (MCH) outcomes. Then, Venkataramanan et al (2022) found that m-health interventions can improve access to MCH. Although Liu and Wang (2021) as well as Ilozumba et al (2018) have discussed mobile applications in supporting maternal health, both of which did not discuss the user interface (UI) and user experience (UX) of mobile applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to date, they have underemphasized outcomes for mothers in the postpartum period. 27,29,30 Digital health tools, however, offer unique promise as a patient level strategy to complement care provided in the formal sector and close the gaps described previously across the pregnancy-postpartum continuum. With high rates of mobile phone penetration across lowincome countries, the prevalence of such interventions has increased in recent decades.…”
Section: Introductionmentioning
confidence: 99%